Comparison of sweet sorghum and cassava for ethanol production by using saccharomyces cerevisiae - Nadir, Najiah; Mel, Maizirwan; Abdul Karim, Mohamed Ismail; Mohd Yunus, Rosli (Asian Network for Scientific Information, 2009)
The two-step enzymatic hydrolysis of sweet sorghum and cassava were performed by commercially available α-amylase and glucoamylase and further ethanol fermentation of the obtained hydrolyzates by Saccharomyces cerevisiae were studied. For both sweet sorghum and cassava, the hydrolysis and fermentation were done in a 2 L stirred tank bioreactor, B-Braun fermenter, by using the same conditions. The amount of glucose obtained after hydrolysis process was greater in sweet sorghum compared to cassava, which are 50.07 and 40.00 g L-1, respectively. Also, sweet sorghum gave higher ethanol concentration than cassava at the 64 h of fermentation process, which are 40.11 and 34.07 g L-1, respectively.